Brain physiology during photoperiod-related caste determination in the primitively eusocial wasp Polistes jokahamae - Ken Sasaki; Hideto Yoshimura; Kakeru Yokoi (Scientific Reports)
Abstract Adult females of the primitively eusocial wasp Polistes jokahamae can change caste in response to photoperiod length. Short-day photoperiod females store more lipids but have less developed ovaries for hibernation (becoming gynes), whereas long-day photoperiod females have fewer lipid stores but more developed ovaries under queenless conditions (becoming egg-laying workers). To explore the physiological mechanisms underlying photoperiod-related caste determination, analyses of gene expression levels in the brains of short- or long-day females were performed. Results suggest that short-day females may exhibit higher expression of genes involved in tryptophan metabolism, insulin signaling, and nutrition, including the digestion of sugars and lipids, and production of royal jelly proteins. Oral administration of tryptophan resulted in a positive correlation between tryptophan levels in the brain and lipid stores in the abdomen, suggesting that tryptophan promotes lipid storage in gynes. Long-day females showed enhanced expression of genes involved in tyramine/dopamine syntheses, epidermal growth factor receptor, insulin degradation, and oogenesis. In these females, tyramine administration increased the brain levels of tyramine and dopamine, and activated initial ovarian development under queenless conditions. Together, these results indicate that photoperiod-related caste determination in P. jokahamae may involve gene expression pathways similar to those involved in caste determination during the preimaginal stage in other Polistes species.